Memahami Peran Komunikasi Perempuan Dalam Perjuangan: Tinjauan Al-Qur'an Pada Kisah Leila Khaled - Rakinten, Abdillah; Nurainun; Hidayatulloh, Rahmawan (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
Communication plays a crucial role, especially for women who often face gender challenges and societal stereotypes. Leila Khaled, a Palestinian female figure, became a symbol of resistance through her brave actions in the name of struggle. This study examines the role of women's communication in the struggle through the perspective of the Qur'an, focusing on the case of Leila Khaled. This study aims to broaden the understanding of women's contributions to history and political struggle and enrich the discussion of Islamic values ​​that support women's active participation. With a qualitative approach and literature study, this study explores how women use communication in the struggle, the challenges they face, and the successes they achieve. The results of this study are expected to provide new insights into effective communication strategies in the struggle, which can be adopted by contemporary movements. In addition, this study also strengthens the understanding of Islam's views on the role of women and makes a significant contribution to the literature on the role of women's communication in the struggle.